EXPERT SYSTEM OF DISEASE DIAGNOSIS IN RABBITS USING CERTAINTY FACTOR METHOD - Wardani, Sisca; Pardede, Akim Manaor Hara; Prahmana, I Gusti (Yayasan Bina Internusa Mabarindo, 2024)
Rabbits are mammals of the family leporidae, which can be found anywhere, rabbits are increasingly popular in the community not to be kept alone even to a profitable side business. Raising rabbits is not new anymore, there are several places that sell and buy rabbits that are very interesting. The development of rabbit farming needs to be considered because of the disease in rabbits caused by several factors including ectoparasites that are late to be handled because of the lack of knowledge of rabbit farmers about the initial action before being brought to the animal clinic, and long distances limit farmers in conducting consultations on handling diseases in rabbits. Therefore, the need for a system to diagnose diseases in rabbits by knowing some of the symptoms early, with this system is expected to be an alternative use of technology that can be used to detect rabbit disease early on quickly, precisely, and accurately, so that for the future treatment of rabbit disease sufferers can be handled more quickly by using the certainty factor method that is more accurate in analyzing data quickly in getting the diagnosis of rabbit disease. From the test conducted with the selected symptoms, namely hair loss, scales on the scalp, the scalp looks cracked, then the highest percentage value of the test results with a value of 100% and diagnosed infectious diseases of the scalp.